Correction to: Cellular effects of glycine and trehalose air-polishing powders on human gingival fibroblasts in vitro (Clinical Oral Investigations, (2022), 26, 2, (1569-1578), 10.1007/s00784-021-04130-0) - Weusmann, Jens; Deschner, James; Imber, Jean-Claude; Damanaki, Anna; Leguizamón, Natalia D. P. [UNESP]; Nogueira, Andressa V. B. (Springer Nature, 2022)
The correct affiliation of the author Anna Damanaki is Department of Periodontology and Operative Dentistry, University Medical Center of the Johannes Gutenberg University Mainz, Augustusplatz 2, 55131, Mainz, Germany The original article has been corrected.